Attitude and Guidelines for Development Cultural Tourism in Communities of Phra Nakhon Si Ayutthaya - Klomklaw, Kanokkarn; Supprasert, Theerasak (Arts of Management Journal, 2024)
The objectives of this article are: 1) to study attitudes regarding the conservation of cultural heritage sites, temples, and ancient sites. 2) to analyze factors affecting attitudes regarding the importance of temples and ancient sites. 3) to study guidelines for the development of cultural tourism in the community of Phra Nakhon Si Ayutthaya Province. This research is mixed-methods research. The tools used to collect data include questionnaires and interviews. The statistics used in data analysis include frequency, percentage, mean, and standard deviation. And inferential statistics are Ordered Logit models. The results of the research found that: 1) Tourists in Phra Nakhon Si Ayutthaya province have a high level of attitude towards preserving the cultural heritage sites of temples and ancient sites in the community. The main reason is that temples and ancient sites are a source of pride for the nation’s cultural prosperity, which has been passed down from generation to generation. 2) Factors affecting attitudes that recognize the importance of temples and ancient sites in the community are tourists who have their own businesses, 1-3 family members, tourists with an income of more than 20,000 baht per month, and travelers by private car. It influences the opportunity for the number of tourists to increase from an attitude towards conservation of cultural tourism. 3) Guidelines for the development of cultural tourism in Phra Nakhon Si Ayutthaya Province rely on: 1) knowing the context of people in the community towards the conservation of tourist attractions, temples, and ancient sites; 2) the potential and strengths of cultural tourism resources that are unique and valuable; 3) the positive impact on the community of cultural tourism; and 4) the results, negatively affecting the community of cultural tourism in Phra Nakhon Si Ayutthaya Province.